2012
DOI: 10.9775/kvfd.2012.6771
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Diffuse Peritoneal Larval Mesocestoides corti (syn. M. vogae) Cestodiasis in A Dog in Turkey

Abstract: SummaryA laparotomy was performed in an eleven years-old female Doberman with loss of appetite, abdominal distension and signs of pain revealed multiple structures of a size reaching 1.5 cm, composed of small (6 mm or less), white, cystoid structures, with a total volume of approximately 2 liters. To follow the development of the parasitic organisms, under microscopic observation, their body fragments were also moving without changing place which came out of the abdominal cavity, these masses were transferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(13 reference statements)
1
2
0
2
Order By: Relevance
“…had just slightly higher divergence in this locus; these included M. corti (GenBank: AF286984 [38]) (with a divergence of 0.3 ± 0.3%) and M. litteratus (GenBank: DQ643000 [40]) (with a divergence of 1.0 ± 0.4%). The 12S rDNA of the analyzed species was also highly similar to those from larvae that were previously isolated from life-threatening infections of dogs in Turkey and identified as M. corti HM011122 [41], with a divergence of 0.7 ± 0.5%, and JN572111 [42], with a divergence of 0.7 ± 0.9%. However, these tetrathyridia clearly do not represent M. corti as other individuals, identified as M. corti by Kashiide et al (GenBank: AB848990 [25]) and Nakao (GenBank: AB031363; unpubl.)…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…had just slightly higher divergence in this locus; these included M. corti (GenBank: AF286984 [38]) (with a divergence of 0.3 ± 0.3%) and M. litteratus (GenBank: DQ643000 [40]) (with a divergence of 1.0 ± 0.4%). The 12S rDNA of the analyzed species was also highly similar to those from larvae that were previously isolated from life-threatening infections of dogs in Turkey and identified as M. corti HM011122 [41], with a divergence of 0.7 ± 0.5%, and JN572111 [42], with a divergence of 0.7 ± 0.9%. However, these tetrathyridia clearly do not represent M. corti as other individuals, identified as M. corti by Kashiide et al (GenBank: AB848990 [25]) and Nakao (GenBank: AB031363; unpubl.)…”
Section: Resultssupporting
confidence: 52%
“…2c). Aypak et al [42] reported abundant acephalic metacestodes alongside numerous empty calcified cysts of a diameter less than 6 mm that were aggregated into multiple free aggregates of 15 mm in diameter in the peritoneum of an examined dog. The dog manifested normocytic normochromic anemia with low red blood cell count and low hemoglobin, and neutrophilic leukocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Die Amplikons wurden sequenziert (LGC Genomics GmbH, Berlin) und per BLAST-Suche mit bekannten Gensequenzen (GenBank-Datenbanken) verglichen. Es ergab sich eine hohe Übereinstimmung (97-99%) zu Mesocestoides-Gensequenzen, die von Hunden und Katzen mit PLZ aus der Türkei (12S rRNA [1,32]), Spanien (nukleäre rRNA-Sequenz [11] bzw. Italien (COI-Sequenz [14]) stammen.…”
Section: Verlauf Diagnosestellung Und Weitere Untersuchungenunclassified
“…Über das Vorkommen der PLZ bei Hunden und Katzen liegen Berichte aus Nordamerika (3,4,7,29), Europa (1,2,9,11,14,23,27,(30)(31)(32) und Japan (15) vor. Dabei gibt es über die Häufigkeit in Patientenpopulationen nur ungenügende Informationen.…”
Section: Diskussionunclassified
“…These animals host a variety of helminth species (15,33). There are many studies about the helminths of cats and dogs living in Turkey and approximately 20 species in cats and 40 species in dogs, a total of 60 helminth species have been reported up to now (5,15,36,37). Some of these parasites, particularly taenids cause economic losses in slaughtered ruminants and Toxocara spp.…”
Section: Introductionmentioning
confidence: 99%